FANBOYS, FANGIRLS, AND GEEKS PANEL - Blodgett, Bridget; Salter, Anastasia; Torrey, KT; Lowe, JSA (AoIR Selected Papers of Internet Research, 2015)
This panel examines the contentious and developing nature of fandom in 21st century media. Within the theme of this year’s conference this panel will examine how fandoms reimagine their relationship to the author generated texts and towards one another as a community. Given that fandom is often viewed as a cohesive and joined community, the authors seek to understand the cracks and faults within this idealized concept. By looking at these areas the panel will examine how the view of a homogenized community of fans falls apart. The papers on the panel express a particular interest in the contentious nature of fandom infighting and its relationship to the broader media field. It covers a broad view of different fandom communities, from video games to Supernatural, and will discuss often marginalized or challenged viewpoints and engage in discussions of the relationship between fan, media, and creator.